Antibody–drug conjugates in urothelial carcinoma: scientometric analysis and clinical trials analysis - Zhang, Meng; Zuo, Yuanye; Chen, Siyi; Li, Yaonan; Xing, Yang; Yang, Lei; Wang, Hong; Guo, Rui (Frontiers in Oncology, 2024)
In 2020, bladder cancer ascended to the 10th most common malignancy and is chiefly a subtype of urothelial carcinoma. For patients with metastatic urothelial carcinoma, the standard first-line treatment remains platinum-based chemotherapy, with immunotherapy serving as an alternative in cases of programmed death ligand 1 expression. However, treatment options become limited upon resistance to platinum and programmed death 1 or programmed death ligand 1 agents. Since the FDA's approval of Enfortumab Vedotin and Sacituzumab Govitecan, the therapeutic landscape has expanded, heralding a shift towards antibody–drug conjugates as potential first-line therapies. Our review employed a robust scientometric approach to assess 475 publications on antibody–drug conjugates in urothelial carcinoma, revealing a surge in related studies since 2018, predominantly led by U.S. institutions. Moreover, 89 clinical trials were examined, with 36 in Phase II and 13 in Phase III, exploring antibody–drug conjugates as both monotherapies and in combination with other agents. Promisingly, novel targets like HER-2 and EpCAM exhibit substantial therapeutic potential. These findings affirm the increasing significance of antibody–drug conjugates in urothelial carcinoma treatment, transitioning them from posterior-line to frontline therapies. Future research is poised to focus on new therapeutic targets, combination therapy optimization, treatment personalization, exploration of double antibody coupled drugs, and strategies to overcome drug resistance.